DNA methylation as prognostic factors in non-muscle-invasive bladder cancer: a systematic review and meta-analysis - Singh, Vishwajeet; Singh, Mukul Kumar; Kumar, Anil; Shrivastava, Ashutosh; Sahu, Dinesh Kumar; Jain, Mayank; Pandey, Anuj Kumar (Oncology Reviews, 2025)
IntroductionEarly prognostication in non-muscle-invasive bladder cancer (NMIBC) is essential for optimizing therapy and follow-up. Epigenetic mechanisms, particularly DNA methylation, have emerged as promising biomarkers for predicting disease outcome.Materials and MethodsA systematic review and meta-analysis were conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to evaluate the prognostic significance of promoter DNA methylation in NMIBC. Comprehensive searches of PubMed, Web of Science, Embase, MEDLINE, and the Cochrane Library (January 2010–October 2022) identified eligible studies. The Newcastle–Ottawa scale was used for quality assessment, and pooled hazard ratios with 95% confidence intervals were calculated using random-effects models.ResultsEleven studies with 3,065 NMIBC patients were analyzed. Promoter methylation was significantly associated with poor progression-free survival (pooled hazard ratios (HR) = 2.88; 95% CI = 2.03–4.09; p < 0.0001) and recurrence-free survival (pooled HR = 2.65; 95% CI = 1.93–3.63; p < 0.0001). Although overall survival showed pathway-specific variation (pooled HR = 0.96; 95% CI = 0.36–2.60; p = 0.94), methylation of adhesion and apoptosis-related genes exhibited the strongest associations. Subgroup analyses revealed a greater prognostic impact in Asian cohorts (p < 0.0001), suggesting regional differences in epigenetic susceptibility.ConclusionPromoter DNA methylation constitutes a robust prognostic biomarker for recurrence and progression in NMIBC, with stronger effects in Asian populations. Standardization of validated gene panels, assay thresholds, and cross-regional prospective validation will be essential for clinical translation. Integrating methylation-based classifiers into risk stratification models could improve individualized management and long-term outcomes in NMIBC.